2016
DOI: 10.17795/zjrms-6446
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Carvacrol on Renal Functional and Histopathological Changes in Gentamicin-Induced-Nephrotoxicity in Rats

Abstract: Background: Nephrotoxicity is one of the most important side effects of the use of gentamicin sulphate (GS) resulted in reactive oxygen species generation. Antioxidant compounds played effective roles in reduction of renal injuries caused by using of gentamicin. Carvacrol is a strong antioxidant compound. Objectives: The aim of this study is to explore the effect of carvacrol inhibition in lesions of gentamicin-induced nephrotoxicity. Materials and Methods:In this experimental study, 32 male mature Sprague-Daw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Samarghandian et al (2016) has suggested an ameliorative effect of CAR against immobilization stressed rats showing decreases in kidney SOD, CAT and GSH levels. Ahmadvand et al (2016) reported that CAR has partial protective effect on gentamicin-induced renal toxicity. They showed a significant decrease in serum urea, but not in CRE levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samarghandian et al (2016) has suggested an ameliorative effect of CAR against immobilization stressed rats showing decreases in kidney SOD, CAT and GSH levels. Ahmadvand et al (2016) reported that CAR has partial protective effect on gentamicin-induced renal toxicity. They showed a significant decrease in serum urea, but not in CRE levels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, focal interstitial and tubular edema, connective tissue infiltration, cortical tubular vacuolization and glomerular observed in his study. Histology results ofAhmadvand et al (2016) suggested diminished tubular necrosis, but no change in leukocyte infiltration Bozkurt et al (2014). showed that CAR plus methotrexate treated rats exhibited decreased tubular degeneration compared to animals treated with methotrexate alone, but the difference was not statistically significant El-Sayed et al (2015).…”
mentioning
confidence: 96%
“…Carvacrol treatment was reported to attenuate the increased levels of urea and creatinine in gentamicin-intoxicated rats. 37 The current results revealed that EMB has a neurotoxic effect.…”
Section: Discussionmentioning
confidence: 51%
“…Gentamicin is the most common antibiotic against gramnegative bacterial infections. One of the main side effects of gentamicin is nephrotoxicity 1 . Impairment occurs in 30% of patients treated with gentamicin 2 .…”
Section: Introductionmentioning
confidence: 99%